Analisis Indeks Kepuasan Pelayanan di Institut Teknologi Kalimantan Semester Gasal Tahun 2021 dan 2022 Menggunakan Wilcoxon Rank Test - Salsabila, Alfiyyah; Salamah, Umi; Nurlaily, Diana (Equiva Journal, 2024)
The Service Satisfaction Index (IKP) is an important indicator in evaluating the quality of service in educational institutions such as the Kalimantan Institute of Technology (ITK). In the odd semesters of 2021 and 2022, ITK has made a number of efforts to improve the quality of services provided to students. In this analysis, the sample used is the service satisfaction index at ITK in the odd semesters of 2021 and 2022 using the Wilcoxon Rank Test method for find out whether there is a significant difference between the Service Satisfaction Index in the two semesters. From the results of the analysis using the Wilcoxon method, the decision result was obtained, namely rejecting H0, namely that the IKP value for the odd semester in 2021 was better than the IKP for the odd semester in 2022.